Kepala Sekolah Sebagai Pemimpin Pembelajaran Dalam Implementasi Kurikulum Merdeka Pada Sekolah Penggerak Kabupaten Rote Ndao - Bali, Engelbertus Nggalu; Anin, Serly Arniani; Margiani, Kristin (Haumeni Journal of Education, 2023)
Abstract English The independent curriculum is learning where children will be stimulated according to their interests, talents and potentials, early childhood learning with the freedom of learning at the PAUD level has the aim of exploring the greatest potential of educators and students. This study used a type of descriptive qualitative research. The subjects of this study were 4 principals who were driving schools of Rote Ndao Regency. The data collection method uses interviews, observation and documentation. Data analysis techniques used in this study are data collection, data reduction, data presentation and conclusions. The results of the study showed that the principal's leadership in the implementation of the independent curriculum in Rote Ndao Regency driving schools, as the principal's motivator provided support and enthusiasm for the heads of teachers to accept developing an independent learning curriculum, Principals at driving schools in Rote Ndao Regency also collaborate to improve the development of the independent learning curriculum in this case they collaborate in the preparation of teaching modules and matters related to the independent learning curriculum, the principal also provides training and development, in this case the principal shares good practices and provides ideas related to the independent learning curriculum.